Beyond the pandemic: physical activity and health behaviors as predictors of well-being among Filipino tertiary students - Campoamor-Olegario, Lizamarie; Camitan, Desiderio S.; Guinto, Maria Luisa M. (Frontiers in Psychology, 2025)
IntroductionThis study investigates the relationship between positive health behaviors, physical activity, and well-being among 2,620 Filipino tertiary students, highlighting their enduring significance beyond the pandemic. While conducted in a post-quarantine context, the emphasis on the broader role of health behaviors in supporting student well-being, particularly amid academic pressures, mental health challenges, and sedentary lifestyles in an increasingly digital world, upholds the relevance of the study.MethodsInformed by the PERMAH model incorporating positive emotions, engagement, relationships, meaning, achievement and health in the investigation of well-being, the study employed multiple regression analysis to assess the impact of demographic variables, physical activity levels, and positive health behaviors on overall well-being. The predictor variables included physical activity, nutrition, relaxation, and preventive behaviors, with well-being as the outcome variable.ResultsFindings revealed that the covariates of physical activity, nutrition, relaxation, and preventive behaviors moderately explained 30% of the total variability in post-pandemic well-being. Positive health behaviors significantly predicted the well-being components of positive emotions, engagement, meaning, accomplishment, and health scores. However, no significant associations were found among relationship, nutrition, and physical exercise scores.ConclusionThe results highlight the potential of positive health behaviors in shaping student well-being to address ongoing academic, mental health, and lifestyle challenges in tertiary education. The study underscores the need for holistic, evidence-based interventions integrating physical activity, nutrition, relaxation, and preventive behaviors into student support systems. While causality cannot be inferred, the findings assert the value of comprehensive health initiatives in fostering resilience and overall well-being. Future research is recommended to explore the interplay between nutrition, cognition, and mood, promote healthier campus environments, and develop targeted interventions for stress management and lifestyle improvement in academic settings.